Population Pharmacokinetics of Fosfomycin in Critically Ill Patients - Parker, Suzanne L.; Frantzeskaki, Frantzeska; Wallis, Steven C.; Diakaki, Chryssa; Giamarellou, Helen; Koulenti, Despoina; Karaiskos, Ilias; Lipman, Jeffrey; Dimopoulos, George; Roberts, Jason A. (Antimicrobial agents and chemotherapy, 2015)
This study describes the population pharmacokinetics of fosfomycin in critically ill patients. In this observational study, serial blood samples were taken over several dosing intervals of intravenous fosfomycin treatment. Blood samples were analyzed using a validated liquid chromatography-tandem mass spectrometry technique. A population pharmacokinetic analysis was performed using nonlinear mixed-effects modeling. Five hundred fifteen blood samples were collected over one to six dosing intervals from 12 patients. The mean (standard deviation) age was 62 (17) years, 67% of patients were male, and creatinine clearance (CL CR ) ranged from 30 to 300 ml/min. A two-compartment model with between-subject variability on clearance and volume of distribution of the central compartment ( V c ) described the data adequately. Calculated CL CR was supported as a covariate on fosfomycin clearance. The mean parameter estimates for clearance on the first day were 2.06 liters/h, V c of 27.2 liters, intercompartmental clearance of 19.8 liters/h, and volume of the peripheral compartment of 22.3 liters. We found significant pharmacokinetic variability for fosfomycin in this heterogeneous patient sample, which may be explained somewhat by the observed variations in renal function.